2016
DOI: 10.1038/hortres.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Cucurbita pepo metabolism throughout fruit development in acorn squash and oilseed pumpkin

Abstract: Both the fruit mesocarp and the seeds of winter squash can be used for consumption, although the focus of breeding efforts varies by cultivar. Cultivars bred for fruit consumption are selected for fruit mesocarp quality traits such as carotenoid content, percent dry matter, and percent soluble solids, while these traits are essentially ignored in oilseed pumpkins. To compare fruit development in these two types of squash, we sequenced the fruit transcriptome of two cultivars bred for different purposes: an aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 72 publications
4
18
0
Order By: Relevance
“…Here we observed that the major carotenoid of ripe acorn squash fruits was β-carotene (accumulating up to 23 µg/g FW), while lutein content was low ( Figure S3). These results are consistent with previously described carotenoid levels of acorn squash [21] and of other squash having orange flesh [11]. Two other carotenoid peaks were detected which might be xanthophylls, but further research is required to identify them.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here we observed that the major carotenoid of ripe acorn squash fruits was β-carotene (accumulating up to 23 µg/g FW), while lutein content was low ( Figure S3). These results are consistent with previously described carotenoid levels of acorn squash [21] and of other squash having orange flesh [11]. Two other carotenoid peaks were detected which might be xanthophylls, but further research is required to identify them.…”
Section: Discussionsupporting
confidence: 92%
“…During fruit development and ripening, sugars, starch and carotenoids accumulate and significantly affect fruit sweetness, texture and nutritional values, respectively [20][21][22]. Fruit acidity in pumpkin and squash is low (0.04-0.3% of FW, pH 6.8) and has no effect on the fruit sensory quality [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Brix is used in programs as a proxy for sweetness, and % dry matter is related to starchiness ( Corrigan et al 2001 ; Loy 2004 ). As the starch and sugar pathways are known to be interrelated, it is not suprising that Brix and % dry matter would have high estimated genetic correlations ( Wyatt et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the first Cucurbita transcriptome was generated using 454 GS FLX Titanium technology [28]. Subsequently, many differentially expressed genes associated with flowering, disease resistance, fruit size, fruit shape, fruit color, fruit sweetness, fruit nutritional qualities, and chilling sensitivity were determined using RNA-seq [29,31,32,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%